Fitness for duty: a 3-minute version of the Psychomotor Vigilance Test predicts fatigue-related declines in luggage-screening performance - Basner, Mathias; Rubinstein, Joshua (Journal of occupational and environmental medicine, 2011)
To evaluate the ability of a 3-minute Psychomotor Vigilance Test (PVT) to predict fatigue-related performance decrements on a simulated luggage-screening task (SLST). Thirty-six healthy nonprofessional subjects (mean age = 30.8 years, 20 women) participated in a 4-day laboratory protocol including a 34-hour period of total sleep deprivation with PVT and SLST testing every 2 hours. Eleven and 20 lapses (355-ms threshold) on the PVT optimally divided SLST performance into high-, medium-, and low-performance bouts with significantly decreasing threat detection performance A'. Assignment to the different SLST performance groups replicated homeostatic and circadian patterns during total sleep deprivation. The 3-minute PVT was able to predict performance on a simulated luggage-screening task. Fitness-for-duty feasibility should now be tested in professional screeners and operational environments.